Kathmandu-centric Dateline of Nepali Media - Paudel, Shree Ram (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
It has been almost a decade since the federal system started to be practiced in Nepal, ending the centralized governance system. But there is no reflection of federal structure in media sector. Kathmandu-based main stream media are still operating with centralized mindset. This study has employed theoretical framework of diversity in democratic governance. Qualitative approach has been used to analyse issue after key informant interviews and content analysis of four national dailies consisting government owned and privately operated. The study shows that the front pages of newspapers are widely dominated by the Kathmandu-centric bylines and the media contents are predominantly Kathmandu-centric.